Ultra-fast Joule heating synthesis of homogeneous copper-based bimetallic catalysts for electrochemical nitrate-to-ammonium reduction in wastewater treatment - Su, Jenn Fang; Hoang, Minh-Son; Setiabudi, Herma Dina (Elsevier, 2025)
The conversion of nitrate to ammonia presents a promising solution to reduce the energy consumption and carbon footprint associated with the traditional Haber-Bosch process, while also addressing the environmental impacts of nitrate-containing wastewater. To tackle the challenges in catalyst preparation for efficient electrochemical nitrate reduction toward ammonium, this study reports an extremely rapid Joule-heating synthetic method to fabricate a series of copper (Cu)-based bimetallic catalysts. The results demonstrate that the Joule-heating process leads to the formation of well-dispersed and homogeneous bimetallic particles as evidenced by the scanning electron microscope (SEM) and corresponding energy dispersive spectroscopy (EDS), exhibiting an enhanced catalytic activity. Among various samples, the homogeneous copper-nickel (CuNi) catalyst presents an exceptional ammonium selectivity of 98 %, an ammonium yield of 49 %, and an ammonium formation rate of 764 µg h−1 cm−2, which are approximately 2 times higher than Cu monometallic catalyst. This superior activity is attributed to the increased electrochemical active surface area (ECSA) in CuNi materials. Additionally, X-ray photoelectron spectroscopy (XPS) characterization confirms the electronic redistribution within the CuNi structure, revealing a lower oxidation state of Cu, which further contributes to the improved efficiency in the nitrate reduction reaction. Overall, this study enables a new route for the rational design of homogenous bimetallic catalysts in nitrate reduction for wastewater treatment and environmental protection.